1985
DOI: 10.1099/0022-1317-66-2-295
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on the Role of Neuraminidase and the Mechanism of Low pH Dependence in Influenza Virus-induced Membrane Fusion

Abstract: SUMMARYThe role of neuraminidase and the mechanism of low pH dependence in influenza virus-induced membrane fusion have been studied further using fowl plague virus (FPV, H7N 1). Two specific anti-FPV neuraminidase antisera obtained from chickens immunized with recombinant virus strains inhibited viral neuraminidase activity without influencing its haemagglutinating activity. These sera totally inhibited the FPV-induced fusion of erythrocytes and partially reduced haemolysis. But both fusion and haemolysis act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 19 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…Similarly a recent study (Huang et al, 1985) has indicated a role for the target membrane in dictating the exact pH optimum for fusion of influenza virus with red blood cells.…”
Section: Discussionmentioning
confidence: 82%
“…Similarly a recent study (Huang et al, 1985) has indicated a role for the target membrane in dictating the exact pH optimum for fusion of influenza virus with red blood cells.…”
Section: Discussionmentioning
confidence: 82%
“…The enzyme has also been suggested to play a role in initiation of infection, either by promoting fusion activity (Huang et al, 1980(Huang et al, , 1985 or by releasing sialic acids from oligosaccharides that may interfere with the binding to cellular receptors near the receptor-binding site (Ohuchi et al, 1995). The HEF protein of influenza C virus is known to bind cellular receptors containing 9-O-acetyl-5-N-acetylsialic acids as the major receptor determinant and releases the acetyl residue from position C-9 of the substrate (Herrler & Klenk, 1987 ;Rogers et al, 1986).…”
Section: Inhibitor Acetylesterase Activity (%)mentioning
confidence: 99%
“…Sialidase is also involved in the breakdown of the mucosal lining of the upper respiratory tract during the initial infection and contributes to the release of the virion by the budding process [23,28]. This enzyme hydrolyses ·-O-ketoglycosidic linkages of terminal sialic acid residues on glycoconjugates of viral and cellular origin which would otherwise cause HA-mediated self-aggregation of the virus particles [17]. The spike NA is a 200-to 240-kD tetrameric structure, presenting a hydrophilic region with antigenic and catalytic sites and a hydrophobic one that is inserted into the virion lipid envelope [10].…”
Section: Introductionmentioning
confidence: 99%